USP37 Promotes Lung Cancer Cell Migration by Stabilizing Snail Protein via Deubiquitination - Cai, Jiali; Li, Mengying; Wang, Xiang; Li, Lei; Li, Qi; Hou, Zhaoyuan; Jia, Hao; Liu, Shiyuan (Frontiers in Genetics, 2020)
Snail is a prominent EMT transcription factor and promotes metastasis. However, Snail protein is unstable and is quickly degraded through ubiquitination-mediated proteasome pathway. Deubiquitinases prevents Snail degradation by regulating the ubiquitination-mediated hydrolysis process. Our studies demonstrate that DUB family member, USP37, can deubiquitinate Snail and prevent degradation of Snail. USP37 is colocalized with Snail in the nucleus. Biologically, Up-regulated expression of USP37 promotes lung cancer cell migration, while depletion of Snail abolishes the effect of USP37. These data demonstrate that USP37 is a Snail specific deubiquitinase and also indicate a potential therapeutic target for metastasis.